Effectiveness of caregiver-provided individual cognitive interventions in older adults with dementia - Silva, R.; Bobrowicz-Campos, E.; Santos-Costa, P.; Cardoso, R.; Bernardo, J.; Santana, E.; Almeida, I.; Loureiro, R.; Cardoso, D.; Apóstolo, J. (Journal of Alzheimer's Disease Reports, 2023)
Background: In a society increasingly committed to promoting an active life in the community, new resources are needed to respond to the needs of citizens with Alzheimer’s disease and other forms of dementia. The potential of several individual cognitive interventions to be provided by caregivers has been explored in the literature. Objective: To synthesize the best available evidence on the effectiveness of caregiver-provided individual cognitive interventions in older adults with dementia. Methods: Systematic review of experimental studies on individual cognitive interventions for older adults with dementia. An initial search of MEDLINE and CINAHL was undertaken. Another search for published and unpublished studies was performed on major healthcare-related online databases in March 2018 and updated in August 2022. This review considered studies that included older adults with dementia, aged 60 years and over. All studies that met the inclusion criteria were assessed for methodological quality using a JBI standardized critical appraisal checklist. Data were extracted using a JBI data extraction form for experimental studies. Results: Eleven studies were included: eight randomized controlled trials and three quasi-experimental studies. Caregiver-provided individual cognitive interventions had several beneficial effects in cognitive domains, including memory, verbal fluency, attention, problem-solving, and autonomy in activities of daily living. Conclusion: These interventions were associated with moderate improvements in cognitive performance and benefits in activities of daily living. The findings highlight the potential of caregiver-provided individual cognitive interventions for older adults with dementia